CHALLENGES OF HIGHER EDUCATION AS A PUBLIC SERVICE DURING THE DURATION OF THE COVID-19 PANDEMIC FROM THE PERSPECTIVE OF STUDENTS - Dujmović Bocka, Jelena; Bakota, Boris; Romić, Danijela (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2022)
In this paper the authors are presenting key challenges of higher education as public service during the duration of the COVID-19 pandemic. The aim of the paper is to examine the opinions of regular and part-time students about organization of classes during the pandemic. The key hypothesis set in the paper is: Institution of higher education ensures efficiency of the teaching process and retains adequate teacher-student relations during the COVID-19 pandemic. The research included regular and part-time first, second and third year students attending professional undergraduate administrative study program at the Faculty of Law in Osijek and Administrative Study at College of Applied Sciences Lavoslav Ružička in Vukovar. The research results were used for the purposes of confirming or disproving the hypothesis formed in the paper. Descriptive statistics was used for the analysis of research results. Scientific contribution to administrative science is evident in units where authors provide theoretical background for conducting empirical research at the Faculty of Law in Osijek and College of Applied Sciences Lavoslav Ružička in Vukovar, where they analyze key challenges which teachers and students are facing, where they make final conclusions and suggestions for improving the organization of the teaching process in extraordinary circumstances in the future.